Inclusive Data for Resilience: - Riosa, Meili; Swasto, Eko; Dewi Candraningrum (Salasika, 2024)
This research, conducted by Plan Indonesia, YAKKUM Emergency Unit (YEU), and the Klaten Association of Disabled People (PPDK), with support from ELRHA, UKAid, the Norwegian Ministry of Foreign Affairs, and Plan International, aimed to foster inclusive research by integrating Views from the Frontline (VFL) guidelines with the Feminist Participatory Action Research (FPAR) method. The study involved women, people with disabilities, including youth and children with disabilities, as well as the elderly. The research participants included people with disabilities, the elderly, health cadres, and elderly cadres. The research was conducted from May to December 2023 in the disaster-prone areas of Kemalang and Manisrenggo Districts, Central Java. Data analysis was done through triangulation, utilizing multi-party meetings to verify findings based on various times, places, and participants. The research identified types of threats related to the Merapi volcano eruption and needs based on the Humanitarian Inclusion Standard, focusing on gender, age, and ability. Key recommendations include integrating disaster risk management approaches with community-led action plans, enhancing inclusion, promoting local leadership, and developing a national advocacy strategy to increase community involvement in disaster risk reduction efforts, particularly for women, the elderly, and people with disabilities.